Consequences For Nigeria's Democracy and the Cost Of Governance. - Ajiteru, S.A.R; Sulaiman, T.H; Abalaka, J.N (International Forum of Researchers and Lecturers, 2025)
President Goodluck Jonathan established the Presidential Committee on Rationalization and Restructuring of Federal Government Parastatals, Commissions, and Agencies in August 2011 in an effort to reduce the growing cost of government. The committee, led by Stephen Orosanye, the former Head of the Civil Service of the Federation, produced a report that included various recommendations, some of which have caused uncertainty and anxiety among government workers. The committee reviewed existing legislation and noted in the report that